2010
DOI: 10.1038/oby.2009.251
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Visceral Fat in Midlife Women: The Study of Women's Health Across the Nation (SWAN) Fat Patterning Study

Abstract: Visceral fat (VF) increases with the menopause and is an independent predictor of the metabolic syndrome, diabetes, and cardiovascular disease (CVD) in women. Little is known about how hormonal changes during the menopausal transition are related to the increase in VF. We aimed to determine the relationship between bioavailable testosterone and VF in middle‐aged women at various stages of the menopausal transition and whether this relationship is independent of age and other CVD risk factors. The Study of Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
157
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(179 citation statements)
references
References 46 publications
9
157
0
13
Order By: Relevance
“…De acordo com Janssen et al 13 , mulheres na pós-menopausa possuem maior acúmulo de gordura visceral do que as que ainda menstruam, sendo independente do processo de envelhecimento. O estrogênio é considerado como fator protetor para doenças cardiovasculares nas mulheres pré-menopáusicas, e devido à redução deste hormô-nio em mulheres após a menopausa ocorre maior suscetibilidade ao aumento de gordura na região abdominal.…”
Section: A Síndrome Metabólica Na Transição Menopáusicaunclassified
“…De acordo com Janssen et al 13 , mulheres na pós-menopausa possuem maior acúmulo de gordura visceral do que as que ainda menstruam, sendo independente do processo de envelhecimento. O estrogênio é considerado como fator protetor para doenças cardiovasculares nas mulheres pré-menopáusicas, e devido à redução deste hormô-nio em mulheres após a menopausa ocorre maior suscetibilidade ao aumento de gordura na região abdominal.…”
Section: A Síndrome Metabólica Na Transição Menopáusicaunclassified
“…41,47 In another study, including pre-, peri-and postmenopausal women, high BT and low SHBG levels were also found to be associated with an increase in visceral fat, independently of age, insulin resistance and estradiol. 78 As all studies used a cross-sectional design, the causal direction of the reported associations cannot be ascertained. The reversal direction, for instance, is supported by studies showing a decrease in testosterone levels after weight and body fat loss in overweight women.…”
Section: Cardiovascular Risk Factors and Diseasementioning
confidence: 99%
“…However, some studies have shown that upon controlling for VAT, the relationship between metabolic variables and SHBG and/or bioavailable testosterone is no longer found (14)(15)(16). Furthermore, others have postulated that it is the bioavailable testosterone that regulates VAT accumulation associated with CVD risk, and may even directly contribute to CVD risk (10,17).…”
Section: Introductionmentioning
confidence: 99%
“…In the SWAN study (10), it was shown that bioavailable testosterone was the strongest predictor of VAT, whereas sex hormone-binding globulin (SHBG) was just as strong an inverse predictor of VAT, independent of race, total percent body fat, and other CVD risk factors. Given the strength of the relationship between VAT and bioavailable testosterone and its inverse relationship with SHBG, it would be important to determine if androgenic steroids have an independent effect on metabolic risk.…”
Section: Introductionmentioning
confidence: 99%